ChemInform Abstract: Ternary Aurides RE4Mg3Au10 (RE: La, Ce, Pr) and RE4Cd3Au10 (RE: Y, La—Nd, Sm, Gd—Dy) — Ordering Variants of the Zr7Ni10 Type. Issue 10 (February 2016) - Johnscher, Michael; Block, Theresa; Niehaus, Oliver; Poettgen, Rainer
Abstract: Ln 1 4 Mg3 Au10 (Ln 1 : La, Ce, Pr) and Ln 2 4 Cd3 Au10 (Ln 2 : Y, La—Nd, Sm, Gd—Dy) are prepared by induction melting of the elements (Nb tubes, 1.